BPJS Kesehatan dalam Perspektif Hukum Islam (Studi Fatwa Majelis Ulama Indonesia dan Fatwa Nahdlatul Ulama) - Mughni Labib (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
This paper elaborates the fatwa of the Healthcare and Social Security Agency (BPJS Kesehatan) issued by the Indonesian Ulema Council (MUI) and Nahdlatul Ulama (NU), Indonesia’s largest Muslim organization. The MUI and NU declared their own fatwa on BPJS Kesehatan. The MUI labeled that BPJS Kesehatan contravened Islamic law, whereas the NU promoted that the national health insurance aligns with the law. These two fatwas trigger polemic in the country. A qualitative study was designed by employing usul al-fiqh (Islamic jurisprudence) and sociological approaches. The study used documentation and interviews to collect data concerning the MUI and NU fatwas on BPJS Kesehatan. The interactive model of Miles & Huberman was adopted to analyze the data. The results reveal that the issuance of the MUI and NU contradictory fatwas against BPJS Kesehatan was due to the use of different Islamic sources (dalil) and overlooks in drafting the edicts. The MUI emphasized more on several elements involved in the health insurance that were inconsistent with sharia law such as riba (interest), gharar (uncertainty), and maisir (gambling). Conversely, the NU highlighted a formal aspect stipulating that BPJS Kesehatan represented a social agency that benefited lots of people. This study also points out that some factors causing the variety of fatwas on BPJS Kesehatan between the MUI and NU covered the understanding and application of the dalil in relation to the edict formulation and the influence of socio-political atmospheres at the time of fatwa issuance.